Pengaruh Good Corporate Governance, Leverage, dan Sales Growth terhadap Tax Avoidance dengan Ukuran KAP sebagai Pemoderasi - Hanum, Khalida; Gusmiarni, Gusmiarni; Suratman, Adji (Jurnal Akuntansi dan Governance, 2024)
Objectives: Analyze the effect of independent commissioners, audit committees, institutional ownership, managerial ownership, leverage, and sales growth on tax avoidance with KAP size as a moderator.Design/method/approach: Using a quantitative approach with 18 samples of consumer goods industry companies listed on the Indonesia Stock Exchange for the period 2013-2022 so that 180 data are obtained and using moderated regression analysis (MRA) as a moderation test using the Eviews 12 application.Results/findings: The results showed that independent commissioners and audit committees did not affect tax avoidance. Institutional ownership, managerial ownership, and leverage have a positive effect on tax avoidance. Sales growth has a negative effect on tax avoidance. KAP size cannot moderate the effect of independent commissioners, audit committees, institutional ownership, managerial ownership, leverage, and sales growth on tax avoidance.Theoretical contribution: It is hoped that this research can increase accounting knowledge and become the basis for further tax avoidance research.Practical contribution: As a direction for companies so that the policies decided are appropriate and the determination of the amount of tax paid to the state does not violate the rule of law..Limitations: Tax avoidance in this study only uses 18 samples of goods and consumption industry companies